Pharmacist’s age affect information provided for pharmacy clients about generic substitution - Lewek, Pawel; Śmigielski, Janusz; Banaś, Izabela; Kardas, Przemyslaw (Journal of Medical Science, 2017)
Introduction. According to WHO, increase in usage of generic drugs may be one of the ways to reduce costs of healthcare systems around the world. However, according to scientific data, physicians and pharmacists doubt in their effectiveness – the reason for that is not well known. Due to this fact an evidence of factors affecting their opinion is being searched for. Aim. The aim of this study was to assess whether correlation exist between the age of pharmacist and the way information about generic drugs is provided. Material and Methods. This was a questionnaire-based study. Especially prepared questionnaire was made available to pharmacists of Lodzkie province. Survey was conducted in Lodz (81.8%) and other towns of lodzkie province. Results. One hundred and forty eight pharmacists working in Lodzkie province have answered the questionnaire (84.5% women and 13.5% men, aged 23–59, working mainly in private pharmacies – 89.1%). Most of pharmacists (47; 31.8%) younger than 35 years provided information about generic drugs, after being asked about it. Most of pharmacists older than 35 years had given information before patients asked them about it. Correlation analysis revealed that strong statistically significant correlation between pharmacist’s age and the moment when he provides an information about generic drugs exist (P < 0.05). Conclusions. Age of pharmacists affect their commitment to provide information about generic drugs for pharmacy clients.